Doing business in Lithuania - Reischl, Václav (2016)
The bachelor thesis examines the business environment of the Lithuanian Republic in respect to the potential investor, who would consider investing his capital into the country. Firstly the historical background and the demographical development of the country are examined. Secondly the thesis includes the PEST analysis of the Lithuania. The four environments, which are the political, economic, social and technological are examined in order to give one a detailed overview of the Lithuanian market. Lastly the SWOT analysis is used to examine the performance of a Lithuanian company.